Management of Body Condition Score between Pregnancy Scanning and Lamb Marking Impacts the Survival of Triplet-Bearing Ewes and Their Lambs. - Haslin E; Allington T; Blumer SE; Boshoff J; Clarke BE; Hancock SN; Kearney GA; Kenyon PR; Krog J; Kubeil LJ; Lockwood A; Refshauge G; et al. (MDPI (Basel, Switzerland), 2023)
This study evaluated the impacts of management of body condition score (BCS) between pregnancy scanning and lamb marking on the mortality of triplet-bearing ewes and their lambs at 19 research sites across Southern Australia. Triplet-bearing ewes of Maternal (crossbred or composite) or Merino breed were randomly allocated to treatment at pregnancy scanning at an average of 97 days from the start of joining: High or Low BCS. The BCS of individual ewes was assessed at pregnancy scanning, pre-lambing (average of 137 days from the start of joining) and marking (average of 165 days from the end of joining), and ewe and lamb mortality to marking, recorded for each mob. The average BCS at pregnancy scanning was 3.4 for Maternal ewes and 3.3 for Merino ewes. There were no breed by BCS treatment effects on the BCS of ewes at pregnancy scanning or lamb marking or on the change in BCS between pregnancy scanning and pre-lambing or between pre-lambing and marking. The change in BCS differed between the High and Low BCS treatments, between pregnancy scanning and pre-lambing (0.12 vs. -0.33; p < 0.001) and between pre-lambing and marking (-0.39 vs. 0.07; p < 0.001) but did not differ between breeds. The average BCS at marking for ewes managed at the High and Low BCS treatments was 3.1 and 3.0 for Maternals and 3.0 and 2.8 for Merinos. Survival of triplet-bearing Merino ewes (p < 0.01) and their lambs (p < 0.001) was greater when ewes were managed at the High BCS compared to the Low BCS. The BCS treatment did not impact the survival of Maternal ewes or their lambs. The survival of Merino but not Maternal lambs was higher when ewes were in greater BCS pre-lambing (p < 0.01) and when ewes gained BCS between pregnancy scanning and pre-lambing (p < 0.01). Ewe mortality was lower when ewes gained BCS between pregnancy scanning and pre-lambing (p < 0.05). Merino ewes were more likely to die than Maternal ewes for a given change in BCS between pregnancy scanning and pre-lambing (p = 0.065). Overall, our findings demonstrate that producers should manage the nutrition of triplet-bearing Merino ewes so that ewes are in greater BCS at lambing and/or to gain BCS between pregnancy scanning and lambing to improve ewe and lamb survival. Triplet-bearing Maternal ewes should be managed to gain BCS between pregnancy scanning and lambing to improve ewe survival.
Keywords: Maternal ewes; Merino ewes; body condition score; ewe mortality; lamb survival; triplet